Peran Kearifan Lokal Masyarakat Merangin dalam Pembentukan Karakter Siswa Sekolah Dasar di SD Negeri 001/VI Bangko - Egi Agustandi; Shobrina Fitri; Muhammad Ali Imron; Diva Apri Mulya; Vivin Anisa (PT. Penerbit Tiga Mutiara, 2026)
Character education among elementary school students is becoming increasingly complex due to social change, technological development, and weakening connections between students and local culture. Merangin local wisdom has the potential to serve as a foundation for contextual character education; however, research that conceptualizes it as an integrated ecosystem in elementary schools remains limited. This study aims to analyze the forms of Merangin local wisdom, mechanisms for integrating them into learning and school culture, family and community involvement, and supporting and inhibiting factors in its implementation at SD Negeri 001/VI Bangko. This study employed a qualitative approach with a case study design through observations, semi-structured interviews, and documentation involving the principal, teachers, students, parents, and community leaders. Data were analyzed interactively through data reduction, data display, and conclusion drawing and verification. The findings indicate that values of mutual cooperation, deliberation, responsibility, care, politeness, and togetherness are transformed through culture-based learning, exemplary practices, habituation, cultural projects, and social activities. The novelty of this study lies in its conceptual model of local wisdom as a character education ecosystem integrating schools, families, communities, and responses to digital challenges.